Acute hemiplegia as initial presentation in FIP1L1-PDGFRA-rearranged myeloid neoplasm with eosinophilia: a case report - Cheng, Min; Shi, Wenjie; Xu, Jin; Wei, Doudou; Sun, Yue; Jiang, Qian; Li, Yongjie (Frontiers in Oncology, 2026)
BackgroundMyeloid neoplasms harboring the FIP1L1-PDGFRA (F/P) fusion gene infrequently manifest as acute cerebral infarction. The F/P fusion gene induces proliferation within the eosinophilic lineage, resulting in a clonal hypereosinophilic syndrome that may lead to cerebral infarction. This condition demonstrates a high responsiveness to imatinib therapy.Case presentationA 27-year-old man presented with acute hemiplegia and was found to have significant eosinophilia. Neuroimaging revealed acute-subacute infarcts with concurrent focal stenosis of the right middle cerebral artery. He was diagnosed with F/P-rearranged myeloid neoplasm associated with myeloid sarcoma. Treatment with low-dose imatinib monotherapy (100 mg/day) resulted in rapid resolution of both eosinophilia and the vascular stenosis. Over 9 years of follow-up without adjuvant antithrombotic agents, he has maintained sustained molecular remission and normal neurological function, with no recurrent stroke.ConclusionThis case provides new clinical data for the diagnosis and treatment of this type of eosinophilia, and highlights the importance of early recognition, workup, and treatment. Peripheral hypereosinophilia may cause tissue damage, leading to hypereosinophilic syndrome with cerebral infarction. F/P+ clonal hypereosinophilic syndrome is a rare diagnosis to consider in patients with unexplained cerebral infarction and hypereosinophilia. In these instances, it is imperative to conduct a peripheral blood test for the F/P fusion gene early in the diagnostic evaluation of hypereosinophilic syndrome. Upon confirmation of the diagnosis, initiation of imatinib therapy should occur promptly. This treatment approach has resulted in a swift and sustained complete cytologic and molecular remission, no recurrence of cerebral infarction, obviating the need for intensive chemotherapy, statins, anticoagulant or anti-platelet agents.